Eosinophilic ulcer of the tongue in an 80-year-old Iranian woman after a psychologically stressful event. (14th February 2013) - Akhavan, Ali; Mosavi, Ali; Jarrahi, Mohammadreza; Navabii, Hossein
Abstract : Eosinophilic ulcer of the oral mucosa is a benign self-limiting, chronic lesion more frequently seen in the oral cavity or tongue that can mimic squamous cell carcinoma. The pathogenesis of this problem is unknown. In this paper, we present a case of an 80-year-old woman with eosinophilic ulcer of the tongue after a psychologically stressful event.